Characteristics of equilibrium states in the models of struggle between alternative opponents in the presence of external assistance only to individual players - Karataieva, T.; Koshmanenko, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We determine the characteristics (type, number, position in the phase portrait, and stability) of the equilibrium states of a dynamical system simulating the competition between individuals in an abstract society a  part of which receives external assistance. By analyzing a system with three individuals as an example, we determine the detailed description of the dependence of phase portrait of the system on the values of the parameter of assistance and its bifurcation thresholds for two cases where assistance is provided only to one or to two players. For possible applications, we propose an interpretation of the equilibrium states as compromises in the conflict competition of social clusters.